Peri-urban landscapes in metropolitan regions: using transdisciplinary research to progress towards an improved conceptual and geographical understanding - Ramos, I.L. (2020)
Peri-urban areas are diverse and complex landscapes. It is this complexity that is being recognized as the ground for the capacity to provide answers to the emerging global challenges, such as climate change, food security and the well-being of an increasingly urban population. Peri-urban areas have been rather neglected in regional and urban planning: they were perceived as a space for urban sprawl and the location of regional and trans-regional infrastructures. Despite the renewed attention being given to peri-urban areas, these remain geographically and conceptually ill-defined. This paper aims to contribute to this debate by approaching peri-urban landscapes from a transdisciplinary perspective. It does so by gathering different views as held by a panel of experts and a group of stakeholders on how peri-urban areas can be defined, what is unique about them and, ultimately, which criteria should be used in its definition. The obtained results made it possible to present the diversity of perspectives, as well as the common views. Together, these may provide better understanding towards the development of a new planning agenda for peri-urban landscapes